PENGARUH TOTAL ASSET TURNOVER DAN DEBT TO ASSET RATIO TERHADAP RETURN ON ASSET PADA PT SAMPOERNA AGRO TBK PERIODE 2010-2024 - Ulhaq, Aqilah Diah; Muhamad Restu Wijaya (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
This study aims to determine the effect of Total Asset Turnover and Debt to Asset Ratio on Return On Asset at PT Sampoerna Agro Tbk during the period 2010–2024, both partially and simultaneously. This study utilizes secondary data in the form of the company's annual financial reports obtained from the official website of PT Sampoerna Agro Tbk. The research method employed is quantitative. Data analysis was conducted using descriptive statistics, classical assumption tests, linear regression tests, t-tests, F-tests, and the Adjusted R-square coefficient of determination test. The results of the study indicate that, partially, Total Asset Turnover has a significant positive effect on Return On Asset, as evidenced by thitung 6.000 > ttabel 2.179 with a sig value of 0.000 < 0.05. Meanwhile, Debt to Asset Ratio has a significant negative effect on Return On Asset, as evidenced by thitung -5.179 > ttabel 2.179 with a sig value of 0.000 < 0.05. Simultaneously, Total Asset Turnover and Debt to Asset Ratio have a significant effect on Return On Asset, as evidenced by the value of 16.475 > 3.81 and a significant value of 0.000 < 0.05.